URGENSI PENCATATAN WAKAF MENURUT HUKUM POSITIF - Laila Nisfi Ayuandika; Nurul Asri Safitri; Rizki Alya Zahra; Selfi Wahyu Saputri (Prodi Hukum Keluarga Islam (Ahwal Asy-Syakhsiyyah) Fakultas Syariah Unisba, 2022)
Waqf as a legal action related to the interests of the community has the potential for the emergence of a violation, whether committed by nadzir as waqf manager, heir, or by other parties. In practice, waqf that occurs in people's lives has not been fully and efficiently run so that in many cases the waqf property is not properly maintained. The government made an effort by issuing Law No. 41 of 2004 concerning waqf which is expected to be a solution to answer the problems that arise. So the purpose of this study is to determine the urgency of recording waqf according to positive law, this study uses a qualitative descriptive method and the approach that the author uses in this study is normative juridical, namely an approach using the provisions of Positive Law in Indonesia